2013
DOI: 10.1177/0049475512472440
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral gangrene in Plasmodium vivax malaria: a rare manifestation

Abstract: Symmetrical peripheral gangrene (SPG) is an extremely rare complication of malaria that has been well described in multiple case reports of Plasmodium falciparum and mixed infection. We present a case of malaria with isolated Pl. vivax infection complicated by SPG. This index case is the first reported case of peripheral gangrene involving bilateral hands and feet in Pl. vivax infection in an adult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…We report a case of isolated P. vivax malaria presenting with DIC manifesting as SPG. This case is unusual because DIC and SPG have been reported extremely rarely in the literature in association with isolated P. vivax malaria [57]. Amputations were required in all reported cases to date, however, in the present case, our patient recovered completely with antimalarial and conservative treatment emphasizing the role of early diagnosis and initiation of treatment.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…We report a case of isolated P. vivax malaria presenting with DIC manifesting as SPG. This case is unusual because DIC and SPG have been reported extremely rarely in the literature in association with isolated P. vivax malaria [57]. Amputations were required in all reported cases to date, however, in the present case, our patient recovered completely with antimalarial and conservative treatment emphasizing the role of early diagnosis and initiation of treatment.…”
Section: Introductionmentioning
confidence: 58%
“…However, there have been very few reports of an association of SPG with isolated P. vivax malaria infection. Arora et al [5] reported the index case of malaria with isolated P. vivax infection complicated by SPG involving bilateral hands and feet. Two other cases [6, 7] were reported of patients presenting with similar complications later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Autopsy often reveals thrombi concentrated in the small vessels and not the large vessels. [4,5,8,18] No treatment is universally satisfactory. Rather, treatment should be guided by the underlying disease and the patient's general condition.…”
Section: Discussionmentioning
confidence: 99%
“…[1] With the reemergence of malaria, such rare but unique complications of malaria have been observed from time to time and reported mainly from India. [2345] A few such cases or complications are also reported in Plasmodium vivax [4] and mixed[5] malaria also. Exact pathogenesis could not be ascertained.…”
mentioning
confidence: 99%